2019
DOI: 10.1021/jacs.8b12554
|View full text |Cite
|
Sign up to set email alerts
|

Anion Transport with Pnictogen Bonds in Direct Comparison with Chalcogen and Halogen Bonds

Abstract: In this communication, we introduce transmembrane anion transport with pnictogen-bonding compounds and compare their characteristics with chalcogen-and halogen-bonding analogs. Tellurium-centered chalcogen bonds are at least as active as antimony-centered pnictogen bonds, whereas iodine-centered halogen bonds are three orders of magnitude less active. Irregular, voltage-dependent single-channel currents, high gating charges, efficient dye leakage and small Hill coefficients support the formation of bulky, memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
113
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(114 citation statements)
references
References 50 publications
0
113
0
1
Order By: Relevance
“…21 Advances in the eld of hydrogen-bond donor anionophores have inspired parallel efforts based on chloridophilic main group compounds. [22][23][24][25][26][27] Owing to their elevated and welldocumented anion affinity, antimony derivatives have drawn attention. In a recent study, Matile and co-workers showed that SbPh(C 6 F 5 ) 2 is an active chloride anion transporter that interacts with the anion via pnictogen-bonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Advances in the eld of hydrogen-bond donor anionophores have inspired parallel efforts based on chloridophilic main group compounds. [22][23][24][25][26][27] Owing to their elevated and welldocumented anion affinity, antimony derivatives have drawn attention. In a recent study, Matile and co-workers showed that SbPh(C 6 F 5 ) 2 is an active chloride anion transporter that interacts with the anion via pnictogen-bonding.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Matile and co-workers showed that SbPh(C 6 F 5 ) 2 is an active chloride anion transporter that interacts with the anion via pnictogen-bonding. 24 Based on the understanding that such interactions are greatly strengthened by oxidation of the antimony center, 28,29 our group concomitantly introduced a family of stibonium cations (C) 30,31 whose anion transport activity is controlled both by the Lewis acidity of the antimony centre and the lipophilic exterior projected by the aryl substituents. 25 Our interest in main group-based anion receptors 32,33 has also led us to consider the use of sulfonium cations for anion capture via chalcogen-bonding, [34][35][36] as in the case of D which forms an isolable uoride anion complex.…”
Section: Introductionmentioning
confidence: 99%
“…The development of small drug‐like molecules capable of mediating selective transmembrane anion transport remains imperative, and is a field of intensive research . Most of these molecules have been designed by applying knowledge acquired through the development of anion receptors, coupling natural or synthetic platforms with suitable binding units that operate through conventional or unconventional hydrogen bonds, involving halogen‐, chalcogen‐, or pnictogen‐bonding interactions, or even through anion–π interactions . Beyond anion‐binding strength, the anion‐transport ability of a synthetic receptor is also strongly dependent on its ability to partition into the lipid bilayer, that is, its partition coefficient, which can be tuned by the addition of structural motifs with different lipophilicities, such as alkyl chains, aromatic groups, or fluorinated units .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, interactions involving aromatic rings (π–π, C–H⋯π, lone pair–π, ion–π) are also commonly used in both fields [ 11 , 12 , 13 , 14 ] being more relevant those involving electron-rich and/or electron-poor π-surfaces, since they exhibit stronger interaction energies. Moreover, other more unconventional interactions are gaining the interest of the scientific community and are increasingly taken into consideration for the construction of molecular receptors and catalysts [ 15 , 16 , 17 , 18 , 19 , 20 ]. These interactions can be divided into σ–hole [ 21 , 22 , 23 , 24 ] and π–hole interactions [ 25 , 26 , 27 , 28 , 29 ] and are nowadays entered into the toolkit supramolecular chemists.…”
Section: Introductionmentioning
confidence: 99%